2019
DOI: 10.21776/ub.agrise.2019.019.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency Analysis of Sugar Cane Farming in Malang Regency, Indonesia

Abstract: This study aims to analyze the factors that influence sugarcane production in Malang Regency. This reaserach uses stochastic frontier production function. The model is specified which sugarcane production is influenced by amount of seed, the labor used, the amount of fertilizer, land used in sugar cane production, the frequency of ratooncane. The results showed that factors of sugarcane farming production in Malang Regency are influenced significantly by the number of seed, amount of fertilizer used, and ratoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Likewise, the indirect effect of physical variables on income through production is significant at 1%. The area of cultivated land, which is a physical input variable, affects the need for seeds and labor, thereby increasing production and income (Lestari, Hanani, & Syafrial, 2019;Mohr & Kühl, 2021). The increase in production and income further contributes to the improvement of the regional economy (Daniel, 2021;Susilastuti, 2018), so that the interaction of the people of the border areas of Indonesia and Timor-Leste can be optimized to increase income through marketing surplus agricultural produce from the food estate.…”
Section: A Effect Of Physical Variables On Production and Incomementioning
confidence: 99%
“…Likewise, the indirect effect of physical variables on income through production is significant at 1%. The area of cultivated land, which is a physical input variable, affects the need for seeds and labor, thereby increasing production and income (Lestari, Hanani, & Syafrial, 2019;Mohr & Kühl, 2021). The increase in production and income further contributes to the improvement of the regional economy (Daniel, 2021;Susilastuti, 2018), so that the interaction of the people of the border areas of Indonesia and Timor-Leste can be optimized to increase income through marketing surplus agricultural produce from the food estate.…”
Section: A Effect Of Physical Variables On Production and Incomementioning
confidence: 99%
“…In sugarcane cuttings for germination, it requires energy obtained from the addition of glucose, so the germination of the younger shoots will germinate faster than the old shoots. Furthermore, Lestari et al (2019), argued that the highest germination rate was shown at buds number 10, 11, 14 and the yield decreased until the shoots were located at the base of the sugar cane.…”
Section: Number Of Leavesmentioning
confidence: 99%